2016
DOI: 10.1002/pat.3752
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and evaluation of biobased polyester of PTT/PBAT blend: thermal, dynamic mechanical, interfacial bonding, and morphological properties

Abstract: Novel blends were prepared from biobased poly(trimethylene terephthalate) (PTT) and poly(butylene adipate-coterephthalate) (PBAT) using a twin screw extrusion process as a function of different weight ratios. Thermal stability, mechanical, and interfacial properties of PTT/PBAT blends were investigated using a thermogravimetric analyzer and mechanical analyzer. Phase behavior and surface morphology of the blends were characterized using scanning electron microscopy. Interfacial bonding value of the PTT/PBAT bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…However, upon blending the two polymers together an improvement of the thermal stability occurred where the temperature at which 5 wt % degradation takes place improved past both neat polymers (PPC at 232 °C and PHBV at 263 °C) to about 277 °C for all blends. It has been reported that completely and partially miscible polymer blends are capable of improving thermal stability due to the interactions between each component and their phase morphology . There was evidence of a transesterification reaction between the carbonate groups of PPC and the terminal hydroxy groups of PHBV.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, upon blending the two polymers together an improvement of the thermal stability occurred where the temperature at which 5 wt % degradation takes place improved past both neat polymers (PPC at 232 °C and PHBV at 263 °C) to about 277 °C for all blends. It has been reported that completely and partially miscible polymer blends are capable of improving thermal stability due to the interactions between each component and their phase morphology . There was evidence of a transesterification reaction between the carbonate groups of PPC and the terminal hydroxy groups of PHBV.…”
Section: Resultsmentioning
confidence: 98%
“…increasing PBAT content improved the thermal stability. It was stated that chemical interactions such as transesterification and intermolecular forces such as hydrogen bonding between the two polymers dominate the degradation process . As well, the phase morphology between PHBV and PPC or between the crystalline and amorphous phases play a role in the thermal stability of the blends from the hydrogen bonding of the ester and hydroxy groups .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] For instance, the impact strength and other mechanical properties of PLA/polybutylene adipate-coterephthalate (PBAT) blends were shown to increase drastically when compatibilized with functionalities such as epoxides [11] and anhydrides, [12] attributed to strong interfacial adhesion and formation of a dispersed droplet morphology. [18] Novatein has previously been blended with biodegradable polyesters. For example, the impact strength and elongation of polyhydroxybutyrate-co-valerate (PHBV) could be enhanced by up to 120% when plasticized with epoxidized soybean oil.…”
Section: Introductionmentioning
confidence: 99%